Ectopia Cordis in a First‐Trimester Sonographic Screening Program for Aneuploidy. (1st May 2013) - Sepulveda, Waldo; Wong, Amy E.; Simonetti, Luis; Gomez, Enrique; Dezerega, Victor; Gutierrez, Jorge
Abstract : We review the sonographic features, antenatal course, and perinatal outcomes in 7 cases of ectopia cordis diagnosed in the first trimester. Four cases were associated with a large omphalocele (pentalogy of Cantrell) and 2 with a body stalk anomaly. The remaining fetus had isolated thoracic ectopia cordis. Two pregnancies were terminated; 2 fetuses died in utero; 2 infants died after delivery; and 1 died at 3 months of age. We conclude that the diagnosis of ectopia cordis can easily be established during the first trimester. In agreement with the currently available literature, the prognosis of ectopia cordis in our series was uniformly poor.